Exploring the Impact of Sports on social sustainability: an Italian case - Nora Annesi; Chiara Vassillo; Massimo Battaglia; Marco Frey (European Journal of Volunteering and Community-Based Projects)
The impact of sports on sustainability has been explored across various dimensions and the social dimension of such impact is explored in Sport for Development and Peace initiatives (SDP) towards local and third-country communities. However, the lack of data detected by the literature about the third sector activities, is a critical aspect that weaken the whole sector in valorising its impact on the society. In this context, by focusing the research efforts on the sport sector, the paper analysis the impact of no-profit sport organization at national and local level by framing its impact within the 2030 Agenda. Findings can support the management of no-profit organizations to build their activities in line with global priorities and to valorise their social impact. Indeed, this aspect can reinforce the local trust of these organization in relation to the provided impact.